2022
DOI: 10.3389/fonc.2022.1071439
|View full text |Cite
|
Sign up to set email alerts
|

Vascular invasion and lymph node metastasis mediate the effect of CA242 on prognosis in hilar cholangiocarcinoma patients after radical resection

Abstract: BackgroundCarbohydrate antigen 242 has been clinically used as a diagnostic biomarker for pancreatic cancer. However, the prognostic role of CA242 in hilar cholangiocarcinoma (HCCA) has not been identified. Also, it remains unclear to what extents the vascular invasion and lymph node metastasis mediate the effect of serum CA242 on prognosis.ObjectiveThis study aimed to investigate whether vascular invasion and lymph node metastasis mediate the relationship between CA242 levels and clinical prognosis in HCCA pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Preoperative serum carbohydrate antigen 19-9 could be related to regional lymph node metastases and the prognosis of both pCCA and dCCA with a cutoff of 37 U/ml ( 132 134 ). A recent study reported that elevated serum CA242 (>20 IU/ml) was associated with vascular invasion and lymph node metastasis of pCCA ( 135 ). Furthermore, inflammatory markers including neutrophils, fibrinogen-to-prealbumin ratio, and fibrinogen-to-lymphocyte-to-neutrophil ratio from preoperative peripheral blood were all independent factors for overall survival of eCCA according to the recent multivariate Cox analyses ( 51 ).…”
Section: Biomarkers Of Ecca Novel or Clinicalmentioning
confidence: 99%
“…Preoperative serum carbohydrate antigen 19-9 could be related to regional lymph node metastases and the prognosis of both pCCA and dCCA with a cutoff of 37 U/ml ( 132 134 ). A recent study reported that elevated serum CA242 (>20 IU/ml) was associated with vascular invasion and lymph node metastasis of pCCA ( 135 ). Furthermore, inflammatory markers including neutrophils, fibrinogen-to-prealbumin ratio, and fibrinogen-to-lymphocyte-to-neutrophil ratio from preoperative peripheral blood were all independent factors for overall survival of eCCA according to the recent multivariate Cox analyses ( 51 ).…”
Section: Biomarkers Of Ecca Novel or Clinicalmentioning
confidence: 99%